2015
DOI: 10.1021/acs.jpcb.5b01752
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of DNA by Cisplatin Adducts Results from an Increase in the Rate Constant for the Reaction with Hydrated Electrons and Formation of PtI

Abstract: Pulse radiolysis measurements of the decay of hydrated electrons in solutions containing different concentrations of the oligonucleotide GTG with and without a cisplatin adduct show that the presence of a cisplatin moiety accelerates the reaction between hydrated electrons and the oligonucleotide. The rate constant of the reaction is found to be 2.23 × 10 10 mol −1 L s −1 , which indicates that it is diffusion controlled. In addition, we show for the first time the formation of a Pt I intermediate as a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…When tumor irradiation was performed at 48 h, the ratio of tumor growth delay for the group having the combined treatment compared to delay for the group treated with chemotherapy alone varied from 4.09 to 13.00, depending on the drug. The most efficient combination treatment was observed when the amount of Pt drug binding to DNA was highest, as predicted from fundamental considerations [178][179][180][181][182]. Such results testify our fundamental understanding of the mechanisms of platinum-induced radiosensitization and should have significant impact on the design of more efficient treatment protocols.…”
Section: Transient Anions In Dna Bound To Platinum Chemotherapeutic Asupporting
confidence: 52%
See 2 more Smart Citations
“…When tumor irradiation was performed at 48 h, the ratio of tumor growth delay for the group having the combined treatment compared to delay for the group treated with chemotherapy alone varied from 4.09 to 13.00, depending on the drug. The most efficient combination treatment was observed when the amount of Pt drug binding to DNA was highest, as predicted from fundamental considerations [178][179][180][181][182]. Such results testify our fundamental understanding of the mechanisms of platinum-induced radiosensitization and should have significant impact on the design of more efficient treatment protocols.…”
Section: Transient Anions In Dna Bound To Platinum Chemotherapeutic Asupporting
confidence: 52%
“…The results demonstrated that hydrated electrons induce damage to thymines as well as detachment of the cisplatin moiety from both guanines in the oligonucleotide. The amount of free cisplatin (i.e., the cleavage of two Pt-G bonds) was found to be much larger than that of the products resulting from the cleavage of a single bond [181,182]. The errors represent the deviation of three identical measurements. )…”
Section: Transient Anions In Dna Bound To Platinum Chemotherapeutic Amentioning
confidence: 92%
See 1 more Smart Citation
“…As expected, C>A, C>T and T>A SBSs were strongly reduced on the sense strand (Supplemental Fig. S5) (Fousteri and Mullenders 2008;Harrington et al 2010;Dasari and Tchounwou 2014;Behmand et al 2015;Hu et al 2016). Also consistent with TC-NER, strand bias for C>A, C>T and T>A mutations was stronger in more highly expressed genes (p = 1.45×10 -50 and 1.20×10 -116 , one-sided Chisquared test for all MCF-10A and for all HepG2 clones combined, respectively, Figure 2A, Supplemental Fig.…”
Section: Associations Of Cisplatin-induced Single-nucleotide Substitusupporting
confidence: 82%
“…When cisplatin enters the cells, its two chloride atoms are hydrolyzed, resulting in two positive charges (Masters and Koberle 2003;Behmand et al 2015). Although the hydrolyzed molecule presumably reacts with many molecules in the cell, its therapeutic cytotoxicity is generally considered to stem from reactions with the N7 atoms of purine bases in DNA (Harrington et al 2010;Dasari and Tchounwou 2014;Behmand et al 2015). Most cisplatin-DNA adducts are crosslinks between two adjacent guanines (GpG,65%) or between an adenine and a guanine (5 ′ -ApG-3 ′ , 25%).…”
mentioning
confidence: 99%